Pendampingan Penyusunan Business Plan Untuk Meningkatkan Kreativitas Entrepreneurship Mahasiswa Pendidikan Sejarah - Robbi Kurniawanti, Merci; Wahyuni, Anny; Yosephine Sinurat, Junitas; Mareta, Yoan; Adi Saputra, Muhammad (Pendidikan Sejarah FKIP Universitas JAMBI, 2024)
Abstrak: The problem that occurs among students in the history education study program is that the level of student entrepreneurial creativity is still low, and the minimal output of students who take part in the student entrepreneurship program (PMW). This is because the learning process, especially those that support entrepreneurship values, is still limited to theory and minimal practice. This service activity aims to increase the entrepreneurial creativity of history education students through assistance in preparing business plans. This is in line with the vision of the history education study program, namely to become an entrepreneur based on historical skills. This service activity was carried out in two sessions, the first session was the delivery of material by the resource person and the division into groups guided by the moderator. Next, the second session was the practice of preparing business plans and presentations for each group which were monitored by the team. The result is that there are several draft business plans and product prototypes from each group that have been shared